Assessing practice-based influences on adolescent psychosocial development in sport: the activity context in youth sport questionnaire - Bengoechea, E. G.; Sabiston, C. M.; Wilson, P. M. (Journal of Sports Sciences, 2017)
ABSTRACT: The aim of this study was to provide initial evidence of validity and reliability of scores derived from the Activity Context in Youth Sport Questionnaire (ACYSQ), an instrument designed to offer a comprehensive assessment of the activities adolescents take part in during sport practices. Two studies were designed for the purposes of item development and selection, and to provide evidence of structural and criterion validity of ACYSQ scores, respectively (N = 334; M age = 14.93, SD = 1.76 years). Confirmatory factor analysis (CFA) supported the adequacy of a 20-item ACYSQ measurement model, which was invariant across gender, and comprised the following dimensions: (1) stimulation; (2) usefulness-value; (3) authenticity; (4) repetition-boredom; and (5) ineffectiveness. Internal consistency reliability estimates and composite reliability estimates for ACYSQ subscale scores ranged from 0.72 to 0.91. In regression analyses, stimulation predicted enjoyment and perceived competence, ineffectiveness was significantly associated with perceived competence and authenticity emerged as a predictor of commitment in sport. These findings indicate that the ACYSQ displays adequate psychometric properties and the use of the instrument may be useful for studying selected activity-based features of the practice environment and their motivational consequences in youth sport.